trans-Dichloridobis{dicyclohexyl[4-(dimethylamino)phenyl]phosphane-κP}platinum(II) dichloromethane disolvate - Davis, Wade L. (International Union of Crystallography, 2012)
In the title complex, trans-[PtCl(2){P(C(6)H(11))(2)(4-Me(2)NC(6)H(4))}(2)]·2CH(2)Cl(2), the Pt(II) atom is located on an inversion centre, resulting in a trans-square-planar geometry. Important geometric parameters are the Pt—P and Pt—Cl bond lengths of 2.3258 (6) and 2.3106 (6) Å, respectively, and the P—Pt—Cl angles of 89.64 (2) and 90.36 (2)°. The effective cone angle for the dicyclohexyl[4-(dimethylamino)phenyl]phosphane unit was calculated to be 164°. The compound crystallizes with two dichloromethane solvent molecules; one of which is severely disordered and was treated using the SQUEEZE routine in PLATON [Spek (2009 ▶). Acta Cryst. D65, 148–155].